2006
DOI: 10.1002/pmic.200500133
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of malignant lymphocyte membrane microparticles using double ionization coverage optimization

Abstract: Shed membrane microparticles (MPs) are microvesicles generated from the plasma membrane when cells are submitted to stress conditions. Although MPs reflect the cell state (at least in vitro), little is known on their protein composition. We describe the first set of experiments aiming to characterize the MP proteome. Two ways of triggering MP formation from a T-lymphocytic cell line were analyzed using a 1-D gel approach coupled with LC-MS/MS and the results were compared with those obtained from a classic mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 58 publications
5
107
0
1
Order By: Relevance
“…This could be related to the different MP compositions as functions of their origin, as shown in the proteomic analyses from platelet and leukocytic MPs. 35,36 PrMPs from platelets induced vasodilator products, and this property might protect against vasoconstrictor factors generated by leukocyte PrMPs.…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the different MP compositions as functions of their origin, as shown in the proteomic analyses from platelet and leukocytic MPs. 35,36 PrMPs from platelets induced vasodilator products, and this property might protect against vasoconstrictor factors generated by leukocyte PrMPs.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of proteins found on MPs (which differs between vesiculation stimuli), as well as the level of oxidized lipids, are likely to influence their effects on target cells. 23,24 In addition, in vitro concentrations of MPs should be consistent with those found in vivo for MPs of the same cellular origin.…”
Section: Plasma Levels Of Mps In Cardiovascular Diseasesmentioning
confidence: 99%
“…Proteomic analyses have revealed that the spectrum of proteins found in MPs released in vitro from cultured cells is influenced in part by the type of stimulus used to trigger cell vesiculation. 24 This different pattern of protein expression may be helpful in distinguishing within a subpopulation of circulating MPs those released after apoptotic stimuli from MPs resulting of cell activation. 25 …”
Section: Mp Compositionmentioning
confidence: 99%
“…Molecular profiling approaches using proteomic techniques, performed in order to determine the protein composition of microparticles, have shown that protein composition depends not only on cell type, but also on the conditions of cell stimulation [9,10]. Furthermore, differential lipid composition of microparticles may vary depending on the lipidic environment surrounding cells; thus it is possible that microparticles from patients with metabolic pathologies associated with lipid alterations may have different lipid composition which may account for different functional effects of microparticles on target cells.…”
Section: Introductionmentioning
confidence: 99%